20th Anniversary Update of the Ottawa Decision Support Framework: Part 2 Subanalysis of a Systematic Review of Patient Decision Aids. (May 2020) - Hoefel, Lauren; Lewis, Krystina B; O'Connor, Annette; Stacey, Dawn
Background. The Ottawa Decision Support Framework (ODSF) has guided the development of patient decision aids (PtDAs) for 20 years and needs updating across a range of decisions and hypothesized outcomes.Purpose. To determine the effectiveness of ODSF-developed PtDAs on hypothesized outcomes and to recommend framework changes.Data Source. A subanalysis of randomized controlled trials included in the 2017 Cochrane review of PtDAs comparing PtDAs to usual care in adults considering health treatment or screening decisions (searched to 2015).Study Selection. Trials in the original review that evaluated ODSF-developed PtDAs.Data Synthesis. Meta-analyses of ODSF outcomes with similar measurements and descriptions of other reported outcomes.Results. Of 105 trials, 24 evaluated ODSF-developed PtDAs. Compared with usual care, ODSF PtDAs improved knowledge (mean difference [MD] 13.85; 95% confidence interval [CI] 10.32−17.37; 14 trials), increased accurate risk perceptions (risk ratio [RR] 2.41; 95% CI 1.66−3.48; 7 trials), and increased congruence between informed values and chosen options (RR 1.32; 95% CI 1.09−1.59; 4 trials). They reduced perceived decisional needs as measured using the Decisional Conflict Scale (MD −5.92; 95% CI −8.58 to −3.26; 15 trials) and the proportion of undecided patients (RR 0.65; 95% CI 0.50−0.83; 13 trials). Non-ODSF PtDAs, designed with or without a specific framework, also outperformed usual care. Few ODSF trials measured secondary outcomes.Limitations. The included trials had heterogeneity.Conclusion. ODSF PtDAs address decisional needs and improve decision quality; the best indicator of addressing perceived uncertainty is "proportion undecided." Secondary ODSF outcomes should be reduced to adherence to one's chosen option and use/costs of health services, which warrant further research.